ENHANCING ENTREPRENEURIAL SKILLS OF UNDERGRADUATE SCIENCE, VOCATIONAL AND TECHNICAL EDUCATION STUDENTS THROUGH ENTREPRENEURSHIP EDUCATION - Deba, Ahmad Aliyu; Deba, Abdulkarim Ali; Mallanti, Andi; Jabor, Mohd Khata; Habibu, Abubakar Mohammed (Journal of Technical Education and Training, 2014)
This paper examines the contribution of entrepreneurship education course towards cultivating entrepreneurial skills of undergraduate Science, Technical and Vocational students. The subjects consist of 309 students from the School of Technology Education. Entrepreneurial skills development assessment questionnaire (ESDAQ) was used for data collection. The ESDAQ was validated by experts and internal consistency of 0.80 was obtained using the Cronbach’s Alpha method. The t-test and ANOVA were used for testing hypotheses at the 0.05 significance level. The study reveals that students’ participation in the entrepreneurship education during their undergraduate education stimulates the acquisition of entrepreneurial skills. Entrepreneurial skills of technical education students is higher compared to vocational and science students. Diversification of instructional approach in teaching entrepreneurship education was recommended, especially the use of experiential learning methods interchangeably with the conventional style.